Functionalized aromatic esters of the Amaryllidaceae alkaloid haemanthamine and their in vitro and in silico biological activity connected to Alzheimer's disease - Peřinová, Rozálie; Maafi, Negar; Korábečný, Jan; Kohelová, Eliška; De Simone, Angela; Al Mamun, Abdullah; Hulcová, Daniela; Marková, Jana; Kučera, Tomáš; Jun, Daniel; Šafratová, Marcela; Maříková, Jana; et al. (Bioorganic chemistry, 2020)
A novel series of aromatic esters (1a-1m) related to the Amaryllidaceae alkaloid (AA) haemanthamine were designed, synthesized and tested in vitro with particular emphasis on the treatment of neurodegenerative diseases. Some of the synthesized compounds revealed promising acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitory profile. Significant human AChE (hAChE) inhibition was demonstrated by 11-O-(3-nitrobenzoyl)haemanthamine (1j) with IC50value of 4.0 ± 0.3 µM. The strongest human BuChE (hBuChE) inhibition generated 1-O-(2-methoxybenzoyl)haemanthamine (1g) with IC50 value 3.3 ± 0.4 µM. Moreover, 11-O-(2-chlorbenzoyl)haemanthamine (1m) was able to inhibit both enzymes in dose-dependent manner. The mode of hAChE and hBuChE inhibition was minutely inspected using enzyme kinetic analysis in tandem with in silico experiments, the latter elucidating crucial interaction in 1j-, 1m-hAChE and 1g-, 1m-hBuChE complexes. The blood-brain barrier (BBB) permeability was investigated applying the parallel artificial membrane permeation assay (PAMPA) to predict the CNS availability of the compounds.
Keywords: kinetika; Acetylcholinesterase; estery; Butyrylcholinesterase; Blood-Brain Barrier; simulace molekulového dockingu; cholinesterasové inhibitory; acetylcholinesterasa; Docking studies; Alzheimer’s disease; Amaryllidaceae Alkaloids; butyrylcholinesterasa; Amaryllidaceae; Cholinesterase Inhibitors; fenantridiny; Alzheimer Disease; Haemanthamine; Molecular Docking Simulation; Phenanthridines; vztahy mezi strukturou a aktivitou; Humans; Binding Sites; alkaloidy amarylkovitých; Kinetics; Alzheimerova nemoc; Esters; hematoencefalická bariéra; Structure-Activity Relationship; vazebná místa; lidé